THERMAL EXPANSIVITIES OF SUPERCOOLED HAPLOBASALTIC LIQUIDS - Gottsmann J.; Dingwell D.B. (My University, 2002)
The thermal expansion of supercooled liquids in the haplobasaltic (anorthite-diopside) system have been determined via methods of container-based dilatometry. The expansivity data obtained in this study agree well with estimates provided by previous dilatometric determinations in the system that have relied on alternative experimental strategies. The data have been combined with high-temperature, superliquidus determinations of melt density to obtain expressions for the volume-temperature (V-T) relationships of liquids in the anorthite-diopside system. The V-T data clearly indicate a nonlinear temperature dependence of volume for all melts investigated. The variation is most striking for diopside, where the coefficient of volume thermal expansion decreases ~56% from temperatures near the glass transition to superliquidus temperatures. With increasing anorthite content, the degree of variation appears to decrease. An42Di58 exhibits a decrease of 39% of its coefficient of thermal expansion and An98Di02 of 33%, respectively. The expansivities obtained in this study cannot be reproduced by means of published models that are based on linear V-T relationships. They require instead a reanalysis of existing pressure-V-T equations of state models for silicate melts.